Using technology to access health information: greater WASH knowledge/behaviors in Indonesian mothers. (30th September 2020) - Beckstead, E; Niedfeldt, H; Chahalis, E; Jensen, M; Reher, B; Torres, S; Jusril, H; Rachmi, C N; West, J; Hall, C
Abstract: Background: Despite attention, childhood stunting in Indonesia persists. Proper WASH (Water, Sanitation, and Hygiene) practices help lower childhood stunting. As internet access in Indonesia grows, seeking health information online is increasing. However, research on using technology to increase WASH knowledge and behaviors in Indonesia is limited. The purpose of this study is to assess whether Indonesian women using technology to access health information have higher WASH knowledge and behaviors. Methods: 1, 740 mothers with children under the age of two were randomly selected with three-stage cluster sampling. They were surveyed and interviewed about handwashing and sanitary defecation benefits, steps, and practices. Adjusted and unadjusted logistic and linear regression models were used to compare WASH outcomes between those who used technology to access health information and the control group. The models controlled for mother's age, mother's education, and total household income. Results: Participants who used technology to access health information were more likely to know the benefits (OR = 2.603; CI = 1.666-4.067) and five critical times (OR = 1.217; CI=.969-1.528) of proper handwashing. Mothers were more likely to know the risks of open defecation (OR = 1.627; CI = 1.170-2.264) and understand disease transmission from stool (OR = 1.894; CI = 1.438-2.495). Those using technology to access health information were more likely to report using a gooseneck, squat toilet, septic tank, or closed ground to discard feces than the control group (OR = 3.858; CI = 2.628-5.665). Conclusions: Using technology to access health information was associated with increased handwashing and defecation knowledge and safe elimination of feces. It was not associated with an increase in handwashing with soap. Technology can be used to increase WASH knowledge and behavior, but further research is needed to effectively use technology to increase optimal handwashing behaviors. Key messages: Increasing technology access may encourage good water, sanitation and hygiene behavior change. Using technology to access health information yielded safer defecation practices but not better handwashing practices. Further research is needed.